MUNASABAH AYAT DALAM SURAH AL-QALAM PERSPEKTIF SEMITIC RHETORICAL ANALYSIS (SRA) - Sujiat Zubaidi; Dini Amalia Fattah; Aqdi Rofiq Asnawi (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2023)
The purpose of this research is to examine whether the structure of Surah Al-Qalam exhibits symmetry in accordance with patterns of parallel, concentric, or mirror-symmetrical arrangements at various levels of the text. The research methodology employs analysis, which is used to process data and address the research questions. This research approach adopts the concept of "Coherence" to find coherence in the structure of surah al-Qalam using the Semitic Rhetorical Analysis methodology. This type of library research involves collecting data from various sources such as books, scientific documents, journals, etc. The results of this research show that the application of Semitic Rhetorical Analysis in Surah Al-Qalam produces a series consisting of 3 parts and 8 sections of text structure, which form a mirror concentric construction (AB/x/B’A’). The results of the analysis also show that there is a connection between parts, which shows good coherence and verse structure. This finding refutes Richard Bell's view because each verse in Surah Al-Qalam can be symmetrical with other verses from the lowest to the highest text level.